Identifying Gifted Children: Congruence among Different IQ Measures - Fernández, Estrella; García, Trinidad; Arias-Gundín, Olga; Vázquez, Almudena; Rodríguez, Celestino (Frontiers in Psychology, 2017)
This study has two main aims: 1) analysing the relationship between intellectual capacities and levels of creativity in a sample of Spanish students from the 3rd and 6th grades; and 2) examining the discrimination capacities and degree of congruence among different tests of intellectual ability that are commonly used to identify high-ability students. The study sample comprised 236 primary school students. Participants completed different tests of intellectual ability, which were based on both fluid and crystallized intelligence, as well as creativity. Results indicated that it is advisable to use varying tests in the assessment process, and a complementary measure (i.e. creativity) in order to create a multi-criteria means of detection that can more efficiently distinguish this population of students.